Integrating entrepreneurship into engineering education - Hassan, Marwa Yousif Hassan; Shuriye, Abdi Omar; Hassan Abdalla Hashim, Aisha; Salami, Momoh Jimoh Eyiomika; Khalifa, Othman Omran (Science & Engineering Research Support Society (SERSC), 2017)
Negative economic growth, corrupt governments, and global financial crisis; have attributed to chronic poverty in diverse nations in the world. In fact, this has triggered the Arab uprising, labor strikes and daily common unrest in the west. There must be a solution and not empty promises of creating new jobs and getting people employed that governments have made for ages. To promote entrepreneurship for young generation and integrating these skills into the educational system is one solution. Entrepreneurship is the act of being an entrepreneur, being innovator and introducing new ideas in business. The effort to transform innovation into economic goods and forming new organizations is what we are discussing. The traditional way of engineering education which focuses on technical activities or issues associated with product, service and design has to be reevaluated to include entrepreneurship and business activities. This paper discusses the issue of entrepreneurial engineering education and its importance in economic development in higher learning institutions. Integrating entrepreneurship into engineering education is an imperative domain of technological development for the Muslims’ world. The paper proposes general framework for integrating entrepreneurship into engineering educational system.